The prognosis for delayed immune recovery in HIV-infected children might be associated with pre-cART CD4+ T cell count irrespective of co-infection with tuberculosis - Funsho J. Ogunshola; Ruhul A. Khan; Musie Ghebremichael (BMC Research Notes)
Abstract Background Immune reconstitution following the initiation of combination antiretroviral therapy (cART) significantly impacts the prognosis of individuals infected with human immunodeficiency virus (HIV). Our previous studies have indicated that the baseline CD4+ T cells count and percentage before cART initiation are predictors of immune recovery in TB-negative children infected with HIV, with TB co-infection potentially causing a delay in immune recovery. However, it remains unclear whether these predictors consistently impact immune reconstitution during long-term intensive cART treatment in TB-negative/positive children infected with HIV. Results We confirmed that the baseline CD4+ T cell count is a significant predictor of immune recovery following long-term intensive cART treatment among children aged 0 to 13 years. Children with lower CD4+ T cell count prior cART initiation did not show substantial immunological recovery during the follow-up period. Interestingly, children who were co-infected with TB and had higher baseline CD4+ T cell count eventually achieved good immunological recovery comparable to the TB-negative HIV-infected children. Hence, the baseline CD4+ T cell count at the onset of treatment serves as a reliable predictor of immunological reconstitution in HIV-infected children with or without TB co-infection. Taken together, this follow-up study validates our previous findings and further establishes that initiating cART early alongside early HIV testing can help prevent the diminished CD4+ T cell count associated with inadequate immunological reconstitution.